Chlorination and oxygenation of carbon electrodes for covalent attachment of thiol-terminated molecules - Xin Zheng; Igor L. Bolotin; Beria Tanriover; Kumuditha Rathnayake; Erik J. Askins; Jordi Cabana; Neal P. Mankad; Ksenija D. Glusac (Carbon Trends, 2025)
This study reports covalent edge plane chlorination of carbon electrodes and their subsequent functionalization with thiol-containing redox-active molecules. Specifically, the reactivity of edge C-H groups on glassy carbon (GC) and carbon powder (CP) electrodes with chlorinating reagents, iodine monochloride and iron(III) chloride, was investigated under varying reaction conditions. The degree of chlorination was evaluated using X-ray photoelectron spectroscopy (XPS), solid-state nuclear magnetic resonance (NMR) spectroscopy and vibrational spectroscopy. Chlorination was observed under all tested conditions, with the C-H to C-Cl conversion strongly influenced by electrode pretreatment, reaction time, and type of carbon electrode used. We further investigated the reactivity of surface C-Cl groups in nucleophilic aromatic substitution reactions with (6-mercaptohexyl)ferrocene, (Fc(CH2)6SH). The electrochemical properties of the modified electrodes were compared with those of control samples prepared using anodized carbon and gold electrodes. XPS, infrared spectroscopy, and cyclic voltammetry confirmed the successful thiol-ferrocene functionalization of the chlorinated electrodes, though higher surface coverages were achieved on anodized carbon electrodes. These results indicate that thiols react not only with C-Cl groups but also with oxygen-containing groups present on anodized carbon surfaces. We further explored this reactivity in the use of benzene-1,2,4,5-tetrathiol as a bridging linker to anchor a molybdenum-based complex onto chlorinated and anodized carbon surface.